PEMERIKSAAN CT STONOGRAFI PADA KASUS NEFROLITHIASIS - I Putu Yudha Sambawitasia; Putu Irma Wulandari; Kadek Sukadana (Perhimpunan Radiografer Indonesia (PARI), 2022)
ABSTRACT Background : CT Stonography is a CT scan tract of the kidney that is usually used to detect the presence of stones in the kidney and other pathologies such as the presence of mass in the kidneys. CT Stonography examination with kidney stones case in Buleleng Regional General Hospital using 5 mm slice thickness. The purpose of this study is to know the examination techniques, the reasons for the use of 5 mm slice thickness, and how to determine the size of kidney stones using CT Stonography in cases of nephrolithiasis at Buleleng Regional General Hospital. Methods : This type of research is qualitative with case study approach. The subjects were 2 radiographers, 1 radiologist, and 1 sending doctor. The location of the research at Radiology Installation Buleleng Regional General Hospital. Data were analyzed using by interactive model. Results : From the results of this study examination of CT Stonography at Buleleng Regional General Hospital uses special preparation of 12 hours of fasting before the examination. Position of supine patient (head first). Area scanning from diaphragm to symphisis pubis. Scan parameters using abdomen protocol, 10 mm slice thickness. The reason for using 10 mm slice thickness is that the image can be reconstructed with a thin slice thickness number from the previous result. How to determine the size of kidney stones in patients CT Stonography at Radiology Installation Buleleng Regional General Hospital is using 3 dimensions because to see from the axial, sagittal, coronal multiplanar so that we can measure from the posterior antero direction (AP), cranio caudal (CC), or laterolaterally taken from the widest distance. Conclusion : Examination CT Stonography with nephrolithiasis cases using the position of supine patients (head first), selection of 10 mm slice thickness on CT stonography examination techniques with nephrolithiasis cases at Radiology Installation Buleleng Regional General Hospital for the results of the image can be reconstructed with the amount of thin slice thickness of the previous results. Determination of the size of kidney stones in patients with CT Stonography at Radiology Installation Buleleng Regional General Hospital is using 3 dimensions because to see from the axial, sagittal, coronal multiplanar so that we can measure from the posterior antero direction (AP), cranio caudal (CC), and laterolateral taken from the widest distance.